The martyrdom of Daniel and the Three Youths - Somov, Alexey (Journal for the study of the pseudepigrapha, 2021)
This article investigates the legend about the persecution and martyrdom of Daniel and his three companions at the hand of a wicked Persian king. This story is found in Eastern Orthodox liturgical, hagiographical, and homiletical texts and is based on extracanonical traditions similar to those of the “rewritten Bible” in the Old Testament Pseudepigrapha. The article investigates how the canonical story about Daniel and the Three Youths developed into this account of their martyrdom for Christ. The origins, liturgical function, and textual history of this legend are discussed, as well as its structure and tradition-history. My analysis demonstrates that this legend combines a martyrological account (similar to other stories about Jewish martyrs, for example, Daniel 3, 6; 2 Macc 7) with a reinterpretation of stories about biblical heroes. The legend also includes a resurrection story based on an unexpected exegesis of Matt 27:52–53 and 1 Cor 15:6.